Representasi Identitas Sosial Melalui Fashion Pada Mahasiswa FKIP Universitas Mataram - Noviana Indrianti; Sumitro Sumitro; Mila Noviana (Ulul Albab: Majalah Universitas Muhammadiyah Mataram, 2026)
This study aims to identify the factors that influence students’ fashion choices and the representation of social identity through fashion among students in the Faculty of Teacher Training and Education at Mataram University. This study employs a qualitative approach using the phenomenological method. Data and findings were obtained through observation, interviews, and documentation with informants. The data analysis techniques used followed the theoretical framework of Miles and Huberman, including data reduction, data presentation, drawing conclusions, and verification. The results of this study indicate that students’ fashion choices are influenced by three main factors: personality, social circles, and social media. Personality encourages students to prioritize comfort as the foundation for building self-confidence, while their social environment plays a role in shaping the harmony of their dressing style as a symbol of group cohesion. Additionally, social media serves as a source of inspiration that introduces various fashion trends, thereby encouraging students to adopt a dressing style that aligns with their preferences.